Computational Modeling of Biopharmaceuticals Purification Systems - Rodrigues, Jéssica Maria Dias (2024)
Chromatography is widely used in biopharmaceutical purification, particularly for therapeutic antibodies. However, traditional methods, such as using Protein A resin, are costly and present challenges like ligand leakage and antibody denaturation. Additionally, the process requires large amounts of water and generates significant chemical waste, raising environmental concerns. This thesis focuses on the development of affinity ligands to reduce production costs while maintaining efficiency in antibody purification. By leveraging virtual compound libraries, a scaffold was used to generate millions of potential ligands. This approach reduces the number of experimental candidates while ensuring high chemical diversity. The virtual library was screened to identify ligands with strong binding potential to the antibody. The top-performing ligands were further analyzed to gain insights into their molecular interactions. Two ligands showed strong potential for purification. These findings represent a promising advance toward more sustainable and cost-effective antibody purification.